(3GdUjZ GdbGfhfjI ddYbhO h GdOYGhi GdJLGQjI (B:s (3eOYe HCMcGe GdfbV (B/s - (3GdefGjdj, gGfj eMeO cGeds ((3GdbGgQI(B: s (3EjJQGc ddfTQ hGdJhRjY(B, s, 2010)
(3jMJhi gPG GdcJGH Ydi GTgQ GdUjZ hGdOYGhi hGdWdHGJ GdNGUI HGdTQcGJ GdJLGQjI OYGhj GdGadGS h OYGhj h WdHGJ GdChQGb GdJLGQjI, GdTjc h GdceHjGdI, OYGhj GdTcGJ GdJLGQjI h CMcGe GdfbV GdJLGQjIs
Keywords: (3GdTQcGJ(B--(3bhGfjf hJTQjYGJs; (3GdYbhOs; (3GdYbhO GdJLGQjIs; (3GdbGfhf GdJLGQjs